PENGARUH PENGGUNAAN GAME EDUCAPLAY UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN KEMAMPUAN KOGNITIF PESERTA DIDIK SMP NEGERI 1 ENDE PADA MATERI USAHA DAN ENERGI - Martha Wahan Makin; Yasinta Embu Ika; Antonia Fransiska Laka (LPPM Universitas Nias Raya, 2026)
This study aims to analyze the effect of using the Educaplay game on students’ learning motivation and cognitive abilities at SMP Negeri 1 Ende on the topic of Work and Energy. The research employed a one-group pretest–posttest design involving 20 students as the sample. The instruments used in this study were a learning motivation questionnaire and a cognitive ability test. The results showed that after the implementation of the Educaplay game, students’ learning motivation was categorized as high, with an average percentage of 80.2%. In addition, students’ cognitive abilities improved significantly, as indicated by the increase in the mean pre-test score of 58.00 to a mean post-test score of 87.00. The t-test analysis revealed a Sig. (2-tailed) value of 0.000 < 0.05, indicating a significant difference between the pre-test and post-test scores. Therefore, it can be concluded that the use of the Educaplay game has a positive and significant effect on students’ learning motivation and cognitive abilities.